Perbaikan Teknik Pengemasan Buah-Buahan Segar Untuk Mengurangi Tingkat Kerusakan Mekanis, Studi Kasus di Propinsi Jawa Tengah - Kuncoro Harto Widodo; Suyitno Suyitno; Adi Djoko Guritno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Mechanical damages of fresh fruits may happen in traditional packaging methods. The aim of research is to find some alternatives methods to reduce the mechanical damage during transportation. The variable used in the study are vibration and drop test, and the study was implemented for avocados. mangoes, bananas, and papayas. Using equivalent bruise index percentage, it is known that the packaging models suggested are capable to reduce the mechanical damages (% EBI) from 15,01%-22,33% through 1,57%-9,17%. The result obtained give alternatives for each commodity. The best packaging model for mangoes is the corrugated cartoon, followed by the wooden box V type, the plastic basket and traditional packaging (bamboo basket). Where as for avocados. the best packaging model is the plastic basket, followed by the corrugated. On the other hand, the corrugated cartoon is the best for papayas, followed by the wooden box V type, the plastic basket and traditional packaging (partition). The final result of the result suggests that the wooden box V type is the best for all commodities. This packaging uses a linked hinge which is easier for returning distribution, and surely it needs only little of space on transportation vehicles.